Can short-term conditional subsidies sustain agroecology adoption? Evidence from Zimbabwe - Ngoma, Hambulo; Gebremariam, Gebrelibanos; Zingwena, Taurai; Thierfelder, Christian; Chimonyo, Vimbayi Grace Petrova (CIMMYT, 2025)
Although agroecology is widely regarded as critical for transforming agri-food systems, its adoption remains low. This raises important policy questions about what can be done to nudge adoption. Large-scale input subsidies (ISPs) implemented by most governments are a good avenue. How to implement ISPs to nudge agroecology remains unclear and under explored. We assess the extent to which the Zimbabwean government’s large-scale conditional ISP, Pfumvudza, can sustain agroecology adoption using framed economic field experiments. We found indicative evidence suggesting that the provision of conditional subsidies for two consecutive seasons increased adoption by 5% and sustained it even after the subsidy was withdrawn. Thus, well designed and targeted conditional subsidies have the potential to sustain agroecology adoption.